Preparation method of high-safety lithium battery

By coating the lithium battery separator or positive electrode sheet with a mixed slurry of low-temperature glass powder and solid electrolyte, the short circuit during overheating of the battery is blocked, and the fire and explosion problems caused by thermal runaway of the lithium battery are solved, which significantly improves the safety performance of the battery.

CN119275364APending Publication Date: 2025-01-07JIANGXI GANFENG BATTERY TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411363742.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-28
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Lithium batteries are prone to short circuits when thermally out of control, resulting in fire or explosion. The prior art still cannot effectively block the direct contact of the positive and negative electrodes at high temperatures.

Method used

The mixed slurry is made of low-temperature glass powder, solid electrolyte, binder and wetting agent, and is coated on the surface of the separator or positive electrode sheet to form a coating layer to prevent the short circuit when the battery is overheated.

Benefits of technology

It effectively improves the thermal runaway performance of lithium batteries, reduces the risk of battery fire and explosion, and prevents electrical short circuits inside the battery through the melting of low-temperature glass powder and the high ionic conductivity of solid electrolytes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275364A_ABST
    Figure CN119275364A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a high-safety lithium battery, and relates to the technical field of lithium batteries, the preparation method of the high-safety lithium battery comprises the following steps: S1, preparing low-temperature glass powder, a solid electrolyte, a solvent, a binder, a wetting agent and the like into mixed slurry; s2, uniformly coating the mixed slurry prepared in the step S1 on the surface of a diaphragm in a single-sided or double-sided manner to form a coating layer, and heating and drying to volatilize the solvent to obtain a diaphragm coated with low-temperature glass powder and solid electrolyte; s3, uniformly coating the surface of a positive plate with the mixed slurry prepared in S1 to form a coating layer, and heating and drying to volatilize the solvent to obtain a positive plate coated with low-temperature glass powder and solid electrolyte; and S4, assembling the positive plate, the negative plate and the diaphragm into a battery cell, and when the battery is overheated, melting the low-temperature glass powder to block short circuit of the battery, so that the thermal runaway performance of the battery can be improved, and the fire and explosion risks of the battery are effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and more specifically, to a method for preparing a high-safety lithium battery. Background Art

[0002] With the development of electric vehicles and large-scale energy storage systems, the requirements for battery safety are becoming increasingly higher. As an important component of new energy vehicles and electronic products, lithium batteries provide high energy density and long cycle life, but their safety issues cannot be ignored. Lithium batteries are prone to thermal runaway under thermal, electrical or mechanical abuse conditions, causing fire or explosion.

[0003] When a lithium battery experiences thermal runaway, the diaphragm material inside the battery melts and shrinks at high temperatures, resulting in decreased insulation between the positive and negative electrodes, which can cause a serious short circuit. The commonly used solution is to coat the surface of the diaphragm with Al2O3, boehmite, or a solid electrolyte, which can increase the thermal shrinkage temperature of the diaphragm to a certain extent. However, when the temperature continues to rise, the diaphragm will still shrink, and the positive and negative electrodes of the battery will have direct contact, causing a short circuit. Therefore, it is of great significance to develop a lithium battery that can prevent the positive and negative electrodes of the battery from directly contacting each other during thermal runaway. The present application proposes a method that can prevent the positive and negative electrodes of a battery from directly contacting each other when the battery is overheated, which can effectively prevent the thermal runaway of the battery, thereby improving the safety performance of the battery. Summary of the invention

[0004] The technical problem to be solved by the present invention is that when a lithium battery has thermal runaway, it is easy to cause a serious short circuit. In view of the problems existing in the prior art, a method for preparing a lithium battery with high safety is provided.

[0005] The purpose and effect of the present invention are achieved by the following specific technical means: A method for preparing a high-safety lithium battery, comprising the following steps: S1. preparing a mixed slurry of low-temperature glass powder, solid electrolyte, solvent, binder, wetting agent, etc.; S2, uniformly coating the mixed slurry prepared in S1 on one or both sides of the diaphragm surface to form a coating layer, heating and drying to volatilize the solvent, and obtaining a diaphragm coated with low-temperature glass powder and solid electrolyte; S3, uniformly coating the mixed slurry prepared in S1 on the surface of the positive electrode sheet to form a coating layer, heating and drying to volatilize the solvent, and obtaining a positive electrode sheet coated with low-temperature glass powder and solid electrolyte; S4. Assemble the positive electrode sheet, negative electrode sheet and separator into a battery cell.

[0006] A further preferred solution: the low-temperature glass powder in steps S1 and S2 is a mixture of two or more inorganic materials, and the inorganic materials include SiO2, P2O5, B2O3, Li2O, ZnO, BaO, K2O, Na2O, TiO2, and Li2O; The initial melting temperature of the low-temperature glass powder is 200°C-350°C, and the mass fraction of the low-temperature glass powder in the mixed slurry is 1%wt-30%wt.

[0007] A further preferred embodiment: the solid electrolyte in step S1 is at least one of LATP, LLZO, LLZTO, and LAGP powders, and the mass fraction of the solid electrolyte in the mixed slurry is 0.1%wt-30%wt.

[0008] A further preferred embodiment: the solvent in step S1 is at least one of water, ethanol, N,N-dimethylformamide, N-methylpyrrolidone and anhydrous acetonitrile, and the mass fraction of the solvent in the mixed slurry is 10%wt-60%wt.

[0009] A further preferred embodiment: the binder in step S1 is at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride and hexafluoropropylene, sodium carboxymethyl cellulose, polyacrylate, polyacrylic acid and polyacrylate, and the mass fraction in the mixed slurry is 0.1%wt-20%wt.

[0010] A further preferred embodiment: the wetting agent in step S1 is at least one of polyether-modified silicone and polyol materials, and the mass fraction of the wetting agent in the mixed slurry is 0.1%wt-2%wt.

[0011] A further preferred embodiment: the coating method in steps S2 and S3 is a mixture of one or more of blade coating, gravure roller, transfer coating, and slit coating; The mixed slurry is coated on one side or both sides of the positive electrode sheet.

[0012] A further preferred embodiment: in steps S2 and S3, the heating and drying temperature is 30°C-120°C, the drying time is 5s-740s, and the slurry coating thickness is 1um-8um.

[0013] A further preferred embodiment: the electrolyte injected into the battery cell in step S4 is one of carbonate, carboxylate, ether and ester.

[0014] A further preferred solution: the positive electrode sheet in step S4 is selected from the positive electrode sheet prepared in S3 or a common positive electrode sheet; The diaphragm in step S4 is selected from the diaphragm prepared in S2 or a common diaphragm; When a common positive electrode sheet is used for the battery cell in step S4, the separator is the separator prepared in S2; when a common separator is used, the positive electrode sheet is the positive electrode sheet prepared in S3.

[0015] Beneficial effects of the present invention: Low-temperature glass powder, solid electrolyte, binder, wetting agent, etc. are made into a slurry and coated on the diaphragm or positive electrode. When the battery is overheated, the low-temperature glass powder will melt and prevent the battery from short circuiting. This can improve the thermal runaway performance of the battery and effectively reduce the risk of battery fire and explosion. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The present invention will be further described below in conjunction with the accompanying drawings.

[0017] Figure 1 It is a schematic diagram of the overall structure of the present invention; Figure 2 It is a structural schematic diagram of the present invention; Figure 3 It is a structural schematic diagram of the present invention; Figure 4 It is a structural schematic diagram of the present invention; Figure 5 The following is a comparison table of test structures of the embodiments of the present invention and the comparative examples.

[0018] Figure 1-Figure 4 Middle: positive electrode sheet (1), coating layer (2), separator (3), negative electrode sheet (4). DETAILED DESCRIPTION

[0019] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. The following embodiments are only examples of implementing the present invention. It must be pointed out that the disclosed embodiments do not limit the scope of the present invention. On the contrary, changes and modifications made without departing from the scope of the present invention are all within the scope of patent protection of the present invention.

[0020] See also Figure 1-Figure 5 , a method for preparing a high-safety lithium battery, comprising the following steps: S1. preparing a mixed slurry of low-temperature glass powder, solid electrolyte, solvent, binder, wetting agent, etc.; Furthermore, the solid electrolyte is at least one of LATP, LLZO, LLZTO, and LAGP powders, and the mass fraction of the solid electrolyte in the mixed slurry is 0.1%wt-30%wt; Furthermore, the solvent is at least one of water, ethanol, N,N-dimethylformamide, N-methylpyrrolidone, and anhydrous acetonitrile, and the mass fraction of the solvent in the mixed slurry is 10%wt-60%wt; Furthermore, the binder is at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride and hexafluoropropylene, sodium carboxymethyl cellulose, polyacrylate, polyacrylic acid, and polyacrylate, and the mass fraction in the mixed slurry is 0.1%wt-20%wt; Furthermore, the wetting agent is at least one of polyether-modified silicone and polyol materials, and the mass fraction of the wetting agent in the mixed slurry is 0.1%wt-2%wt.

[0021] S2, uniformly coating the mixed slurry prepared in S1 on one or both sides of the surface of the diaphragm 3 to form a coating layer 2, heating and drying to volatilize the solvent, and obtaining a diaphragm 3 coated with low-temperature glass powder and solid electrolyte; Furthermore, the low-temperature glass powder is mixed by two or more inorganic materials, and the inorganic materials include SiO2, P2O5, B2O3, Li2O, ZnO, BaO, K2O, Na2O, TiO2, and Li2O; The initial melting temperature of the low-temperature glass powder is 200°C-350°C, and the mass fraction of the low-temperature glass powder in the mixed slurry is 1%wt-30%wt.

[0022] S3, uniformly coating the mixed slurry prepared in S1 on the surface of the positive electrode sheet 1 to form a coating layer 2, heating and drying to volatilize the solvent, and obtaining a positive electrode sheet 1 coated with low-temperature glass powder and solid electrolyte; Furthermore, the coating method is a mixture of one or more of blade coating, gravure roller, transfer coating, and slit coating, and the mixed slurry is coated on one or both sides of the surface of the positive electrode sheet 1; Furthermore, the heating and drying temperature is 30° C.-120° C., the drying time is 5s-740s, and the slurry coating thickness is 1um-8um.

[0023] S4, assembling the positive electrode sheet 1, the negative electrode sheet 4, and the separator 3 into a battery cell; Furthermore, the electrolyte injected into the battery cell is one of carbonate, carboxylate, ether and ester; Furthermore, the positive electrode sheet 1 is selected from the positive electrode sheet 1 prepared in S3 or a common positive electrode sheet 1; The diaphragm 3 in step S4 is selected from the diaphragm 3 prepared in S2 or a common diaphragm 3; When the battery cell in step S4 uses a common positive electrode sheet 1, the separator 3 uses the separator 3 prepared in S2; when a common separator 3 is used, the positive electrode sheet 1 uses the positive electrode sheet 1 prepared in S3.

[0024] Low-temperature glass powder has excellent thermochemical stability, which helps maintain the stability of battery components during the electrochemical process, reduces possible side reactions and degradation, and improves the safety of the battery under overheating conditions. Thermal runaway may occur in batteries when they are overcharged, over-discharged, or have an internal short circuit. Low-temperature glass powder can melt at low temperatures and, as an electrical insulating material, can serve as an insulating layer for the battery to prevent electrical short circuits inside the battery, helping to prevent further deterioration of the battery during thermal runaway. Solid electrolytes have high ionic conductivity, good electrochemical stability and high thermal stability, which can effectively prevent thermal runaway of the battery under overheating conditions and improve the safety of the battery. In addition, solid electrolyte coating can serve as an additional protective layer to reduce the side effects that may be caused by overcharging and improve the battery's overcharge resistance. Solid electrolytes have significant advantages in improving battery safety, cycle stability and electrochemical performance.

[0025] In order to further verify the high safety of this lithium battery, the control tests of each group are as follows: Comparative Example 1 Assemble NCM622 positive electrode sheet 1, Li negative electrode sheet 4, ether electrolyte and 12μmPP separator 3 into battery cell A; Assemble a lithium iron phosphate positive electrode sheet 1, a graphite negative electrode sheet 4, a carbonate electrolyte and a 9 μm PE separator 3 into a battery cell B; Example

[0026] Preparation of low-temperature glass powder and solid electrolyte mixed slurry: 2%wt PVDF binder was dispersed in NMP and stirred for 120 min, and then 10%wt low-temperature glass powder, 20%wt solid electrolyte LATP and 0.5%wt polyether modified silicone wetting agent were added to the suspension. The slurry was then placed in a ball mill and ball milled at 400 r / min for 4 h to obtain a glass powder and solid electrolyte mixed slurry S1-1.

[0027] Low temperature glass powder and solid electrolyte coating: The prepared mixed slurry S1-1 was coated on one side of the 39 μm PE separator with a gravure roller to form a coating layer 2. The drying temperature was 85°C and the drying time was 240 seconds to obtain a separator 3 coated with low-temperature glass powder and solid electrolyte. The coating layer 2 had a thickness of 2-3 μm. The prepared mixed slurry S1-1 is coated on the lithium iron phosphate positive electrode sheet 1 with a gravure roller to form a coating layer 2. The drying temperature is 80°C and the drying time is 200s to obtain a positive electrode sheet 1 coated with low-temperature glass powder and solid electrolyte. The coating layer 2 has a thickness of 1-2um.

[0028] Cell preparation: The NCM622 positive electrode sheet 1, the lithium negative electrode sheet 4, the ether electrolyte and the low-temperature glass powder and the PE separator 3 coated with the solid electrolyte are assembled into a battery cell C (the coating steps are as follows Figure 1 ); The lithium iron phosphate positive electrode sheet 1 coated with low-temperature glass powder and solid electrolyte, the graphite negative electrode sheet 4, the carbonate electrolyte and the ordinary PE separator 3 are assembled into a battery cell D (the coating steps are as follows Figure 1 ); The battery cell E is assembled with a lithium iron phosphate positive electrode sheet 1 coated with low-temperature glass powder and solid electrolyte, a graphite negative electrode sheet 4, a carbonate electrolyte, and a separator 3 coated with low-temperature glass powder and solid electrolyte. Example

[0029] Preparation of low-temperature glass powder and solid electrolyte mixed slurry: 2%wt PVDF binder was dispersed in NMP and stirred for 120 min, and then 15%wt low-temperature glass powder, 15%wt solid electrolyte LATP and 0.5%wt polyether modified silicone wetting agent were added to the suspension. The slurry was then placed in a ball mill and ball milled at 400 r / min for 4 h to obtain a glass powder and solid electrolyte mixed slurry S1-2.

[0030] Low temperature glass powder and solid electrolyte coating: The prepared mixed slurry S1-2 was coated on one side of the 12 μm PP separator 3 by a gravure roller, the drying temperature was 85°C, the drying time was 240 seconds, and the separator 3 coated with low-temperature glass powder and solid electrolyte was obtained, and the coating layer 2 had a thickness of 2-3 μm. The prepared mixed slurry S1-2 is coated on the NCM622 pole piece with a gravure roller, the drying temperature is 80°C, and the drying time is 200s to obtain a pole piece coated with low-temperature glass powder and solid electrolyte, and the coating layer 2 has a thickness of 1-2um.

[0031] Cell preparation: Assemble a cell F by using a NCM622 positive electrode sheet 1 coated with low-temperature glass powder and solid electrolyte, a lithium negative electrode sheet 4, an ether electrolyte and a common 12 μm PP separator 3; The lithium iron phosphate positive electrode sheet 1 coated with low-temperature glass powder and solid electrolyte, the graphite negative electrode sheet 4, the carbonate electrolyte and the separator 3 coated with low-temperature glass powder and solid electrolyte are assembled into a battery cell G (the coating steps are as follows Figure 4 ). Example

[0032] Preparation of low-temperature glass powder and solid electrolyte mixed slurry: 2%wt PVDF-HFP binder was dispersed in NMP and stirred for 100 min, and then 20%wt low-temperature glass powder, 10%wt solid electrolyte LLZO and 0.5%wt polyether modified silicone wetting agent were added to the suspension. The slurry was then placed in a ball mill and ball milled at 400 r / min for 4 h to obtain a glass powder and solid electrolyte mixed slurry S1-3.

[0033] Low temperature glass powder and solid electrolyte coating: The prepared mixed slurry S1-3 was coated on both sides of the 39 μm PE separator by a gravure roller, the drying temperature was 85 ° C, the drying time was 240 s, and the separator 3 coated with low-temperature glass powder and solid electrolyte was obtained, and the single-sided coating layer 2 had a thickness of 1-2 μm; The prepared mixed slurry S1-3 is coated on the NCM622 positive electrode sheet 1 by a gravure roller, the drying temperature is 80°C, the drying time is 300s, and the positive electrode sheet 1 coated with low-temperature glass powder and solid electrolyte is obtained, and the coating layer 2 has a thickness of 1-2um; Cell preparation: The NCM622 positive electrode sheet 1 coated with low-temperature glass powder and solid electrolyte, the Li negative electrode sheet 4, the ether electrolyte and the common 9μm PE separator 3 are assembled into a battery cell H; like Figure 3 , assembling a NCM622 positive electrode sheet 1 coated with low-temperature glass powder and solid electrolyte, a Li negative electrode sheet 4, an ether electrolyte and a separator 3 coated with low-temperature glass powder and solid electrolyte into a battery cell I; like Figure 2 , a lithium iron phosphate positive electrode sheet 1, a graphite negative electrode sheet 4, a carbonate electrolyte, a low-temperature glass powder and a separator 3 coated with a solid electrolyte are assembled into a battery cell J.

[0034] In order to examine the safety performance of the AJ lithium-ion battery of the present invention, the present invention verifies the safety performance of the battery cell by means of a needle puncture test and a hot box test: 1. Acupuncture test method: Place the lithium-ion battery in a 25℃ constant temperature box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge the lithium-ion battery that has reached a constant temperature at a constant current of 1C to an upper voltage of 4.3V, and charge it to a current of 0.05C. Transfer the fully charged lithium-ion battery to the nail penetration tester, maintain the test environment temperature at 25℃±2℃, and use a steel nail with a diameter of 5mm to uniformly penetrate the center of the lithium-ion battery at a speed of 25mm / s. Keep it for 1 hour. If the lithium-ion battery does not catch fire, explode, or smoke, it is considered to have passed.

[0035] 2. Hot box test method: After fully charging the battery, the temperature of the test box is raised to 180°C at a rate of 5°C / min and maintained at this temperature for 30 minutes. After the test, observe for 1 hour to check whether the battery has fire or explosion.

[0036] The prepared lithium-ion battery cell AJ was tested, and the test results are shown in Figure 5 ; The present invention prepares a slurry of low-temperature glass powder, solid electrolyte, binder, wetting agent, etc. and applies it on the diaphragm 3 or the positive electrode plate. When the battery is overheated, the low-temperature glass powder can melt to prevent the battery from short circuiting, thereby improving the thermal runaway performance of the battery and effectively reducing the risk of battery fire and explosion.

Claims

1. A method for preparing a high-safety lithium battery, characterized in that: The following steps are involved: S1. preparing a mixed slurry of low-temperature glass powder, solid electrolyte, solvent, binder, wetting agent, etc.; S2, uniformly coating the mixed slurry prepared in S1 on one or both sides of the diaphragm surface to form a coating layer, heating and drying to volatilize the solvent, and obtaining a diaphragm coated with low-temperature glass powder and solid electrolyte; S3, uniformly coating the mixed slurry prepared in S1 on the surface of the positive electrode sheet to form a coating layer, heating and drying to volatilize the solvent, and obtaining a positive electrode sheet coated with low-temperature glass powder and solid electrolyte; S4. Assemble the positive electrode sheet, negative electrode sheet and separator into a battery cell.

2. A method for preparing a high-safety lithium battery according to claim 1, characterized in that: The low-temperature glass powder in steps S1 and S2 is mixed with two or more inorganic materials, and the inorganic materials include SiO2, P2O5, B2O3, Li2O, ZnO, BaO, K2O, Na2O, TiO2, and Li2O; The initial melting temperature of the low-temperature glass powder is 200°C-350°C, and the mass fraction of the low-temperature glass powder in the mixed slurry is 1%wt-30%wt.

3. A method for preparing a high-safety lithium battery according to claim 1, characterized in that: The solid electrolyte in step S1 is at least one of LATP, LLZO, LLZTO, and LAGP powders, and the mass fraction of the solid electrolyte in the mixed slurry is 0.1%wt-30%wt.

4. A method for preparing a high-safety lithium battery according to claim 1, characterized in that: The solvent in step S1 is at least one of water, ethanol, N,N-dimethylformamide, N-methylpyrrolidone, and anhydrous acetonitrile, and the mass fraction of the solvent in the mixed slurry is 10%wt-60%wt.

5. A method for preparing a high-safety lithium battery according to claim 1, characterized in that: The binder in step S1 is at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride and hexafluoropropylene, sodium carboxymethyl cellulose, polyacrylate, polyacrylic acid and polyacrylate, and the mass fraction in the mixed slurry is 0.1%wt-20%wt.

6. A method for preparing a high-safety lithium battery according to claim 1, characterized in that: The wetting agent in step S1 is at least one of polyether-modified silicone and polyol materials, and the mass fraction of the wetting agent in the mixed slurry is 0.1%wt-2%wt.

7. A method for preparing a high-safety lithium battery according to claim 1, characterized in that: The coating method in steps S2 and S3 is a mixture of one or more of blade coating, gravure roller, transfer coating, and slit coating; The mixed slurry is coated on one side or both sides of the positive electrode sheet.

8. A method for preparing a high-safety lithium battery according to claim 1, characterized in that: The heating and drying temperature in steps S2 and S3 is 30° C.-120° C., the drying time is 5s-740s, and the slurry coating thickness is 1um-8um.

9. A method for preparing a high-safety lithium battery according to claim 1, characterized in that: In step S4, the electrolyte injected into the battery cell is one of carbonate, carboxylate, ether and ester.

10. A method for preparing a high-safety lithium battery according to claim 1, characterized in that: The positive electrode sheet in step S4 is selected from the positive electrode sheet prepared in step S3 or a common positive electrode sheet; The diaphragm in step S4 is selected from the diaphragm prepared in S2 or a common diaphragm; When a common positive electrode sheet is used for the battery cell in step S4, the separator is the separator prepared in S2; when a common separator is used, the positive electrode sheet is the positive electrode sheet prepared in S3.

Citation Information

Patent Citations

  • Lithium battery composite diaphragm as well as preparation method and application thereof

    CN114464960A

  • Functional coating for electrode plate, positive electrode plate, preparation method of positive electrode plate and lithium ion battery

    CN115954433A

  • Battery diaphragm as well as preparation method and application thereof

    CN116073072A

  • Slurry for current collector and preparation method of carbon-coated aluminum foil current collector

    CN116387527A

  • Battery diaphragm, preparation method thereof and lithium ion battery

    CN117613514A